Inorganic anion exchanger based on silica with grafted polyhexamethyleneguanidine hydrochloride - Yanovska, E.S.; Dadashev, A.D.; Tertykh, V.A. (Functional Materials, 2009)
Polyhexamethyleneguanidine hydrochloride has been chemically anchored on the surface of amino-containing silica gel preliminarily activated with cyanuric chloride. The possibility of application of the modified adsorbent for extraction and preconcentration V(V), Mo(VI), W(VI) and Cr(VI) anionic forms in acidic media has been demonstrated. Methods of sorption-X-ray fluorescence and sorption-photometric determination of microquantities of these metal-containing anions have been elaborated. Здійснено хімічне закріплення полігексаметиленгуанідинхлориду на поверхні аміновмісного силікагелю, попередньо активованого хлористим ціануром. Показано можливість використання модифікованого адсорбенту для вилучення та передконцентрування аніонних форм V(V), Mo(VI), W(VI) та Cr(VI) у кислотному середовищі, що дозволило розробити методики сорбційно-рентгенофлуоресцентного та сорбційно-фотометричного методів аналізу мікрокількостей металовмісних аніонів. Проведено химическое закрепление гидрохлорида полигексаметиленгуанидина на поверхности аминосодержащего силикагеля, предварительно активированного хлористым циануром. Показана возможность использования модифицированного адсорбента для удаления и предконцентрирования анионных форм V(V), Mo(VI), W(VI) и Cr(VI) в кислой среде, что позволило разработать методику сорбционно-рентгенофлуоресцентного и сорбционно-фотометрического анализа микроколичеств металлосодержащих анионов.